Effects of flow–flame interactions on the stabilization of ultra-lean swirling CH4/H2/air flames. (1st July 2022) - Mao, Runze; Wang, Jinhua; Lin, Wenjun; Han, Wang; Zhang, Weijie; Huang, Zuohua
Abstract: Hydrogen (H 2 ) is regarded as a promising fuel to achieve decarbonization of power and propulsion systems. In this context, hydrogen enriched methane (CH 4 ) combustion has attracted considerable attention in the development of low-emission gas turbines. To achieve low NO x emissions and avoid the dangers of flashback, combustion of CH 4 /H 2 /air mixtures under lean and/or ultra-lean operating conditions is of critical importance, while ultra-lean flames are prone to combustion instabilities and difficult to stabilize even in a bluff-body swirl burner. In this work, a series of confined lean premixed CH 4 /H 2 /air swirling flames with hydrogen enrichment ( α H2 ) ranging from 0 to 80% is investigated under stable and ultra-lean conditions using simultaneous OH-PLIF and PIV measurements. The results suggest that decarbonization of combustion devices requires large volume fractions of H 2 in the fuel mixture, e.g.,  80% H 2 to achieve half CO 2 emission per heat of combustion. It is found that there is a flame topology transition when changing equivalence ratio and/or hydrogen enrichment. At a given α H2, the flames with 0 and 40% H 2 always show "V" shapes, whereas an evolution from "M" to "V" shape can be observed for the 80% H 2 flame when increasing the equivalence ratio. Moreover, at a given ϕ, the flame shape will shift towards "M" shape at α H2 = 80% from "V" shape at α H2 = 0, 40%. Furthermore, H 2 -enriched flames would move to the inner recirculation zone (IRZ) and stabilize there when decreasing ϕ to ultra-lean conditions. Given that hydrogen enrichment can significantly enhance the resistance to flame strain and that under ultra-lean conditions, there is a strong diffusion of hydrogen from the swirling jet to the IRZ where the sufficient residence time and the increase in the local equivalence ratio contribute to the presence of flame pockets and flame stabilization in the IRZ. Highlights: As promising carbon-free fuel, hydrogen is enriched in the fuel blends with large volume fractions (up to 80%). Flame–flow dynamics of confined swirl flames are investigated at extremely lean conditions. Lean flame front exhibits dispersed patchy structure with increased hydrogen enrichment. The H2 -enriched flames would reside in the inner recirculation zone (IRZ) under ultra-lean conditions The higher fuel diffusivity as well as the recirculation strength contribute to the lean flame stabilization.